Analisis Investasi Pengadaan Alat Berat Di PT. Anugrah Halaban Sepakat Dengan Metode NPV dan IRR - Hastia Ulfa; Dedi Yulhendra; Ansosry Ansosry (Departemen Teknik Pertambangan FT UNP, 2018)
On the research of this planning tool to the needs of gali-fit and transport tool that will be discussed are short-term planning for 5 years to the needs of tool gali-fit by using Volvo EC 210 Excavator, Caterpillar 320 D and transport tools by using Nissan CWB 45. PT. Anugrah Halaban agreed to procure the tools dig-load and transport tools the way procurement is done i.e. buy direct and rent and the two methods used certainly has its disadvantages and advantages of each, for it required analysis the most beneficial way with the company, PT Anugrah Halaban agreed procurement tool gali-fit and transport tools. In this research obtained a quantity the cost of ownership and operating costs are different for each of the unit's heavy equipment and there is also a difference in the cost of ownership and operating costs for the leased instrument with the tools that are purchased directly. Cash Flow is obtained, then analyzed by using the method of Net Present Value (NPV) then it can be known whether the alternatives viable economically. For alternative buy cash from existing cash flow then obtained the value of NPV to buy cash alternative is 22523759.00 so the NPV > 0, then the alternative is declared feasible economically. And for alternative rentals from existing cash flow then obtained the value of NPV to rent alternative 22693782.85 is so NPV > 0, then the alternative is declared feasible economically. From peneitian who have 21 days in daptkan the results of the comparison analysis of NPV and IRR can be expressed that alternative procurement tools are most profitable for the company at this time was a lease because the lease is greater than the NPV NPV buy.Keywords: Investment, NPV, IRR, Trial and Error, Owning Cost, Operation Cost